Adapting breastfeeding support in areas of socio-economic deprivation: a case study approach - Louise Hunt; Gill Thomson; Karen Whittaker; Fiona Dykes (BMC, 2021)
Abstract Background There are inequalities in breastfeeding initiation and continuation rates, whereby socio-economically disadvantaged mothers are least likely to breastfeed. Breastfeeding peer support (BPS) interventions are recommended as a solution, and in the UK non-profit organisations are commissioned to deliver BPS services in areas of socio-economic deprivation. BPS interventions have a mixed evidence base, offering limited knowledge about the interaction between context and intervention and how this affects women's experiences. Methods This interpretive study used a case study methodology to explore how and why two BPS services developed their services in socio-economically deprived contexts. Methods aimed to generate holistic understanding of BPS service development. Data collected across both cases comprised; observation (n = 1), and semi-structured interviews with: mothers who had (n = 10) and had not (n = 9) engaged with the BPS services, peer supporters (PSs) (n = 9), community health professionals (n = 5), infant feeding co-ordinators (n = 2), non-profit organisation managers (n = 3), and public health commissioners (n = 2). Inductive grounded theory analytic techniques of open coding and constant comparisons, followed by cross case comparisons, were used to analyse the data. Results The over-arching theme - 'the transcending influence of society' - offers insights into the underlying context and drivers impacting service development. It reflects how funding and data sharing arrangements determined service operation and the peer's access to women. Four underpinning themes explain how: peer supporters were resourceful in adapting their services ('adapting and modifying the support'); BPS organisations worked to enable women's access to supportive breastfeeding environments, but did not necessarily focus service development on the needs of women living in areas of deprivation ('supporting women's journeys to access'); the BPS-professional connections for supporting access and how BPS could result in more supportive community environments ('embedding within healthcare practice'); and how management practices precluded meaningful use of data to provide context led service development ('ways of using knowledge'). Conclusions Findings suggest that while PSs are commissioned to focus on those most in need, there is limited discussion, collection, or use of knowledge about women's lives to develop needs-led service delivery. The key recommendation is the development of a social ecological tool to facilitate the use and application of contextual knowledge.